Review of immune responses correlated with COVID-19 outcomes: the fight, debacle and aftermath in the Indonesian context. - Dian Eurike Septyaningtrias; Jajah Fachiroh; Dewi Kartikawati Paramita; Dewajani Purnomosari; Rina Susilowati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
In the current pandemic, the highly contagious nature of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) leads to an enormous burden for the global health care system and creates challenging socioeconomic problems. Respiratory mucosa, the main entrance of SARS-CoV-2 infection, are equipped with an innate immune defense system as the initial response against infection. Activation of the adaptive immune system facilitates viral clearance as well as providing immunological memory for prevention from subsequent exposure. However, despite repeated efforts at implementing appropriate interventions, severe and fatal cases are continuing to occur and reports of recurrent cases need clarification. Host factors may contribute to the severity of the diseases while viral immune evasion is a common phenomenon leading to severe outcomes and recurrent infection. Discussions of immunological-based tests for screening, herd immunity, along with the possible advantages or potentially futile efforts of development of vaccine and alternative immunotherapy have become a part of daily household conversations. In this review, evidence of innate and adaptive immune responses or lack of them, and immunological problems relevant for SARS-CoV-2 will be summarized. Finally, perspectives for future studies especially in the Indonesian population will be sketched.